(untitled) (Tikrit Journal of Veterinary Science, 2024)
This study examined an anatomical and histological comparison of the esophagus for two types of poultry birds, the Wild ducks and the cogen chicken, the anatomical results showed that the esophagus in both birds is a relatively long, straight, tubular structure with a high capacity for expansion that connects the oral cavity to the stomach, and in ducks it is relatively long and extends on the dorsal side of the trachea. The airway is on the right side of the neck. It has a thin wall and has a high ability to expand because it contains many longitudinal folds, which contribute to absorbing large amounts of food. These folds make it difficult to identify the gizzard. The esophagus consists of two parts, a cervical esophagus and a thoracic esophagus. As for the cogen chicken, the esophagus expands in the middle, forming a part known as the gizzard. It divides the esophagus into two parts, the upper part is called the cervical esophagus. The cervical part, or upper esophagus, represents the upper esophagus part of the esophagus, and the lower esophagus, which is called the thoracic part, is shorter than the upper esophagus. The esophagus is a bulge in the form of a thin-walled sac, consisting of two bilobed lobes, and its wall contains small, prominent folds. In its beginning. Histologically, the esophagus of both birds consists of four tunicates: mucous, submucosal, muscular and serous, and the epithelial layer contains stratified squamousepitheliumIt is wide, and in the Cogen chicken it was almost keratinized, with the presence of simple tubular esophageal glands in both birds in the basic lamina of the wall, and their number was less in ducks than in chickens, and the muscular mucosal layer is not present in ducks, and its presence is limited only to the upper part of the esophagus, which is thin and longitudinal in arrangement. As for the muscular and serous layers, they were in the same tissue arrangement, except for the difference in layer thickness. In ducks, it was thicker.